The Influence of information Technology, Work Experience, Management Participation and HR Competence on the Effectiveness of Accounting Information Systems - Elsa Putri Napitupulu; Herlin Munthe; Nur Ari Sufiawan (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2023)
Analyzing is the aim of this study and proving that there is an influence between Information Technology, Work Experience, Management Participation and HR Competence at Bank BNI Iskandar Muda Branch, BNI USU Branch, BNI Padangbulan Branch and BNI KC Setiabudi, Medan City, North Sumatra. This research utilizes primary data that has been obtained by distributing questionnaires to respondents. The respondents were employees who worked at Bank BNI Iskandar Muda Branch, BNI USU Branch, BNI Padangbulan Branch and BNI KC Setiabudi, Medan City, North Sumatra. Sampling by saturated sample method using a sample of 80 employees. The results of partial testing show that the effectiveness of the accounting information system is positively and significantly influenced by information technology, work experience, management participation and HR competencies at Bank BNI Iskandar Muda Branch, BNI USU Branch, BNI Padangbulan Branch and BNI KC Setiabudi, Medan City, North Sumatra. Simultaneously Information Technology, Work Experience, Management Participation and HR Competence have a positive and significant impact on the Effectiveness of the Accounting Information System at Bank BNI Iskandar Muda Branch, BNI USU Branch, BNI Padangbulan Branch and BNI KC Setiabudi, Medan City, North Sumatra.